Modelling the effect of variable density and diffusion coefficient on heat and mass transfer from a single component spherical drop evaporating in high temperature air streams. (March 2018) - Cossali, Gianpietro Elvio; Tonini, Simona
Highlights: Analytical model of heating and evaporation for single component spherical drop is proposed. The model accounts for the temperature dependence of gas density and diffusion coefficients. The effect of convection is included proposing a modified correlation for the Nusselt number. The model under steady state conditions is compared with the classical approach. Comparison with experimental measurements under transient conditions is discussed. Abstract: Species, energy and momentum conservation equations are solved in spherical symmetry and under ideal gas approximation, to yield an analytical model capable to evaluate the heat transfer and the evaporation rate from a single component spherical drop under quasi-steady conditions, accounting for the temperature dependence of mixture density and diffusion coefficient. The model is applied to predict the evaporation rate from water, acetone, ethanol and three hydrocarbon droplets under temperature conditions of interest for applicative fields, like fire control and combustion. The results from the proposed model are compared with those obtained by the classical model where mass diffusion coefficient and gas density are kept constant to an average value. The proposed model is validated against experimental data from the open literature of transient drop evaporation in high temperature air streams.